REDUCTION OF STUDENT MISCONCEPTIONS USING NEARPOD INTERACTIVE LEARNING PLATFORM BASED ON POSNER'S CONCEPTUAL CHANGE THEORY - Maison, Maison; Purwaningsih, Sri; Pathoni, Haerul; Falah, Hebat Shidow; Putri, Kinanti Eka; Fitriani, Riska; Hidayati, Hidayati (LPPM Universitas Jambi, 2025)
Misconceptions experienced by students must be identified, reduced, and remediated so that they do not become obstacles for students in their learning process. This study aims to reduce students' misconceptions about static fluids using interactive media developed using the Nearpod Platform based on Posner's conceptual change theory. The research design used was a one-group pre-test post-test design study, by conducting a pre-test, providing actions or treatments, and post-tests to 31 sample high school students. The test instruments and interactive media were first developed with a fairly strict validation process regarding content, construct, and face. Data analysis was carried out using the Wilcoxon Signed Rank Test to measure the effectiveness of the learning platform in reducing misconceptions. Based on the results of the study, it can be concluded that the application of the Nearpod interactive learning platform based on Posner's conceptual change theory can significantly reduce students' misconceptions of the material of hydrostatic pressure and Archimedes' law, with a decrease in the percentage of misconceptions from an average of 34.83% in the pretest to 18.06% in the posttest. Therefore, the Conceptual Change Text strategy through Nearpod media has effectively reduced misconceptions.